KARAKTERISTIK PROTEIN DAN ASAM AMINO DAGING RAJUNGAN (Portunus pelagicus) AKIBAT PENGUKUSAN - Agoes Mardiono Jacoeb; Nurjanah .; Lenny Asnita Br Lingga (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
Crabs (Portunus pelagicus) is one member of the class Crustacea that being a major exported commodity. It is exported mostly in form frozen without head and shell and canned pruduct. Steam process is one important step in crab’s canning industry. This research aimed to study the yield, proximate composition, water-soluble protein, salt-soluble protein, amino acids content and the structure of crabs meat’s tissue analysis in a fresh and after steam process. Fresh crabs has higher yield than the steamed one. Steamed crab’s yield decreased by 14.99%. Proximate composition of fresh and steamed crabs as follows, moisture (wb) 78.47% and 75.43%, ash (db) 7.66% and 6.02%; protein (db) 68.09% and 66.63%; fat (db) 0.84%   and 0.75%, charbohydrate (db) 23.41% and 26.62%; water-soluble proteins (db) 40.87% and 25.32%; salt-soluble proteins (db) 58.06% and 30.77%. Crabs meat contained 15 amino acids, 9 essential amino acids and 6 non essential amino acids. The highest essential amino acid composition was arginin by 6.87% in fresh crab and 6.80% in steamed crab, while the highest non essential amino acid composition was glutamate by 10.92% in fresh crab and 9.81% in steamed crab. Fresh crab meat has connective fibers, while the steamed crab meat has  disjointed and not compact fibers.Key words: amino acids, crab (Portunus pelagicus), meat tissue, protein, steaming.